Stabilization of non-noble metal electrocatalysts for acidic oxygen evolution reaction - Cherevko, Serhiy (Current Opinion in Electrochemistry, 2023)
Modern proton exchange membrane water electrolyzers rely on noble metal electrocatalysts. The application of Ir and Pt in such electrolyzers is considered a prerequisite for their long-term operation. However, the scarcity of these critical raw materials is the major drawback of this technology. In recent years, the academic community scrutinized the suitability of non-noble metals as alternative electrocatalysts. While these metals still demonstrate relatively low activity and stability, significant progress has been achieved in improving their performance. Here, we briefly overview recent achievements in oxygen evolution electrocatalysis using non-noble metals. We identify and discuss five stabilization strategies: (a) thermodynamic stabilization; (b) suppression of dissolution kinetics; (c) electrolyte engineering; (d) protection of active interfaces; and (e) system-level solutions. We provide critical remarks on the advantages and drawbacks of the strategies. Moreover, following our previous opinions in this journal, we highlight the significance of testing non-noble metal electrocatalysts in real devices.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Dissolution; Electrocatalysis; Non-noble metals; Stability; Water electrolysis